PERAN KEPALA SEKOLAH DALAM RANGKA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI PENDIDIKAN (STUDI KASUS DI MADRASAH IBTIDAIYAH TAHFIZHUL QUR’AN BAITUL HIKMAH SUKOHARJO TAHUN AJARAN 2022-2023) - Azizah, Miftah Nuril; Sugiyat, S; Sukari, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The purpose of this study is to identify the types of supervision used by the madrasa headmaster, understand how different types of supervision can improve teacher performance, and learn about any challenges the headmaster may have encountered while performing supervision at Madrasah Ibtidaiyah Tahfizhul Qur’an (MITQ) Baitul Hikmah Sukoharjo during the 2022–2023 academic year. A case study design and a qualitative methodology were employed in this investigation. The headmaster and three instructors at MITQ Baitul Hikmah Sukoharjo are the focus of this study. Interviews and documentation studies were the methods employed for collecting data. The headmaster and the three instructors at MITQ Baitul Hikmah Sukoharjo were interviewed for the study, and documentation served as the secondary data source. Data reduction, data display, and conclusion drafting were the methods of data analysis applied. The investigation produced three findings. First, the headmaster has been engaging in a variety of non-routine modes of supervision. Second, the instructors acknowledge that the headmaster's supervision has been successful in raising their performance. Third, the headmaster has been dealing with a number of challenges that may potentially prevent the supervision from being properly implemented in the future.